2006
DOI: 10.1111/j.1574-695x.1997.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of inducible nitric oxide synthase by β-glucans in mice

Abstract: We have already demonstrated that various activities including NO (nitric oxide) synthesis in vivo and in vitro significantly differ between triple helical (SPG) and single helical (alkaline-treated SPG, SPG-OH) beta-glucans. It was previously suggested that the single helical conformer of beta-glucan (SPG-OH) was dominant in cytokine production and subsequent NO synthesis in vitro. In this study, we analyzed production of inducible nitric oxide synthase (iNOS) induced by beta-glucans in vitro and in vivo. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…In both mammals and fish, β-glucan recognition results in the activation of macrophages, which induces phagocytosis, leukocyte migration and the production of cytokines (e.g. IL-1, TNFα), nitric oxide (NO) and reactive oxygen species, as well as the enhancement of complement activity [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In both mammals and fish, β-glucan recognition results in the activation of macrophages, which induces phagocytosis, leukocyte migration and the production of cytokines (e.g. IL-1, TNFα), nitric oxide (NO) and reactive oxygen species, as well as the enhancement of complement activity [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, another two important ␤-glucans, Schizophyllan (SPG) 3 and Lentinan (LNT), having the main chain of (1,3)-␤-glucan with one ␤-(1,6)-glucose branch at every five main-chain glucose residues are clinically used as antitumor agents (22,23). Yadomae and co-workers have demonstrated that SPG could not enhance NO or TNF-␣ secretion, but the alkaline-treated SPG (SPG-OH) could induce NO and TNF-␣ synthesis in vitro and in vivo (24,25). Moreover, SPG-OH augmented NO production in the presence of cytokines such as TNF-␣, IL-1␣, IL-6, GM-CSF, especially in the presence of interferon-␥ (IFN-␥) in vitro.…”
mentioning
confidence: 99%
“…-glucans are acknowledged to be one of the immune response modifiers [6]. Studies conducted over the past decade have shown that -glucans inhibit tumor development [28,38], enhance defense against bacterial infection [15,24], activate macrophages [8], induce production of cytokines [10,34], nitric oxide (NO) and arachidonic acid metabolites [14,21], increase hematopoiesis [35], exert radioprotective effects [12], are effective against burns [9,37], improve wound healing by inducing the macrophage release of wound growth factors [40] and lower serum lipids [4,23]. Among the several mechanisms proposed for the protective effects of -glucans, the major one is related to antioxidant capacity of the molecules [1,20], which has been further proven by Kogan et al [16] using electron paramagnetic response spectroscopy.…”
mentioning
confidence: 99%